Fluvial response to Late Quaternary sea level changes along the Mahanadi delta, east coast of India. (10th July 2020) - Dash, Chinmay; Jaiswal, Manoj K.; Pati, Pitambar; Patel, Narendra Kumar; Singh, Atul Kumar; Shah, Rayees Ahmad
Abstract: This study presents the fluvial response to late Quaternary sea level changes in the Mahanadi delta. Channel morphological adjustments indicative of sea level changes, such asanastomosing-meandering transition, dendritic channels, and river mouth shift, have been used to reconstruct the paleo-coastlines. Major rivers in the Mahanadi delta (e.g., Mahanadi, Devi, Brahmani, and Baitarani) show alteration of anastomosing and meandering fluvial systems at the late Quaternary strandlines. Two generations of dendritic channels, i.e., Early to Mid- (>5 ka) and Mid-to Late (<5 ka) Holocene, have been identified based on OSL ages and affinity to the paleostrandlines. Lateral shift of river mouths in response to sea level changes have been observed in the lower deltaic plain. The delta distributaries such as Bhargavi, Kushabhadra, Brahmani and Baitarani rivers shifted their mouths due to Early to Mid-Holocene (6–7 ka) marine transgression. Different generations of paleochannels in the Mahanadi delta indicate episodes of the delta progradation since Mio-Pliocene. The distributary paleochannels along the Mio-Pliocene strandline indicate the initial stage of Mahanadi delta development. The river morphological response to the changing coastline of the Mahanadi delta is similar to paleo-fluvial morphological adjustments observed along the paleostrandlines of major deltas around the world.